An online diary study testing the role of functional and dysfunctional self-licensing in unhealthy snacking. (1st February 2023) - Sezer, Berke; Öner, Sezin
Abstract: In the present study, we aimed to investigate how two types of self-licensing (functional and dysfunctional self-licensing) are related to unhealthy snack consumption. Self-licensing refers to the act of using justifications before gratifications and has been associated with higher snack consumption. Previous research has found that while functional self-licensing decreases unhealthy snack consumption, dysfunctional self-licensing increases the number of calories taken from unhealthy snacks. Building upon existing evidence, we addressed functional and dysfunctional self-licensing to investigate how self-licensing behaviors are associated with daily variables (i.e., stress and sleep) and unhealthy snacking habits. Participants (N = 124) were given a battery of measures at the start of the week and asked to send their snack consumption every night for a week via an online questionnaire, along with daily stress and sleep items. The data were analyzed with Hierarchical Linear Modelling. Neither self-licensing measures nor unhealthy snacking habits predicted unhealthy snack consumption. Daily stress was associated with lower unhealthy snack consumption. However, the interaction between daily stress and functional self-licensing was significant, suggesting that on stressful days functional self-licensers consume even fewer unhealthy snacks compared to less stressful days. Functional and dysfunctional self-licensing are rather new constructs which is why examining their effects is important for further research. However, in contrast to the existing evidence, we failed to find an effect of both types of self-licensing on snack consumption, suggesting the effect depends on potential contextual or individual-specific factors. Future research using a dieting sample is warranted for a better understanding of how functional and dysfunctional self-licensing operate.